Characterization of Oil and Diesel Waste Modifiers in Lasbutag Asphalt Cold Mix (Aggregated Buton Asphalt Layer) - Artawan, I Putu; Chaerul, Muhammad; Gusty, Sri (ASTONJADRO, 2023)
One of the uses of Buton Asphalt is LASBUTAG which is a road surface with a mixture of Asbuton, modifier and aggregate. Currently, heavy oil as a modifier is scarce in the market, so it is necessary to consider other alternatives as a modifier, one of which can be used, namely waste oil motor vehicle or other machinery. The aim of this study is to analyze the ideal modifier variation in Lasbutag blends using Lombah oil and diesel fuel as modifiers. This research is a quantitative research using experimental methods conducted in the laboratory. The use of the modifier with waste oil and diesel fuel for Lasbutag cold mix pavements can meet the Marshall characteristics required in the special Lasbutag specifications. The stability required in the Lasbutag special specifications is met by using a modifier content of 4.2% to 6.8%, VIM can be achieved at different modifier levels between 4.8% and 7.2%, Cavity Parameters Between Mineral Aggregates (VMA) can be achieved using modifiers from 4% to 7.0% and Melt Value (Flux) can be achieved using modifiers from 4% to 6 .2%. The cold-mixed Lasbutag characteristics required in the Lasbutag special specifications can be met using a modifier between 4.8% and 6.2%, so the most ideal modifier is achieved at 5.5%.